Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1074/jbc.m604081200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mouse Inducible Costimulator (ICOS) Expression by Fyn-NFATc2 and ERK Signaling in T Cells

Abstract: The inducible costimulator (ICOS), a member of the CD28 family of costimulatory molecules, is rapidly induced upon T cell activation. Although the critical role of ICOS in costimulating T cell responses is well documented, little is known of the intracellular signaling pathways and mechanisms that regulate ICOS expression. Here, we report that Fyn, NFAT, and ERK signaling influence ICOS expression as various chemical inhibitors, such as PP2 that targets Src kinases, U0126 that targets MEK1/2, and cyclosporin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 49 publications
(48 reference statements)
3
47
0
Order By: Relevance
“…In contrast to naive T cells, ICOS is constitutively expressed on memory phenotype CD4 ϩ T cells (25) and is also expressed on some subsets of CD25 ϩ CD4 ϩ regulatory T cells (26). Promoter analysis suggests that NFAT and AP-1 may be involved in ICOS gene transcription (27). In contrast, it has been reported that ICOS gene expression is negatively regulated by Roquin (22).…”
mentioning
confidence: 78%
“…In contrast to naive T cells, ICOS is constitutively expressed on memory phenotype CD4 ϩ T cells (25) and is also expressed on some subsets of CD25 ϩ CD4 ϩ regulatory T cells (26). Promoter analysis suggests that NFAT and AP-1 may be involved in ICOS gene transcription (27). In contrast, it has been reported that ICOS gene expression is negatively regulated by Roquin (22).…”
mentioning
confidence: 78%
“…Using mice eradicated of commensal bacteria, we also made the curious observation that re-establishing intestinal colonization with C. albicans alone does not induce ICOS expression by lamina propria CD4 + T cells. Whether this reflects discordant cell activation induced by C. ablicans compared with commensal enteric bacteria through TLR4 or NFAT that each promote CD4 + T-cell ICOS expression is uncertain, but represents an important area for future investigation (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…EL4 cells were plated, transfected with empty or caMEK2 expressing vector, stimulated with PMA and ionomycin, and harvested 16 h later for RNA extraction as described (34). Real-time RT-PCR analyses of il-17a, il17f, and il-22 transcripts were then performed as described above.…”
Section: Transfection Of El4 Cellsmentioning
confidence: 99%